The Effects of Micronutirents on Growth and Yield of Lowland Rice Grown on Typic Dystrudept Soil - Husnain Husnain; Diah Setyorini; Asmarhansyah Asmarhansyah; Andriati Andriati (UNIVERSITY OF LAMPUNG, 2019)
Fertilizers and fertilization technology have important roles in increasing crop production including lowland rice. In response to the issue, a field experiment was conducted to study the effects of micronutrients on growth and yield of lowland rice. The experiment was carried out at Cihideung Ilir Village, Dermaga Sub-district, Bogor Regency from November 2015 until March 2016. The experiment consisted of 8 treatments, namely control (without fertilization), NPK-standard, NPK-standard + ¼ dosage of Hortigro Rice fertilizer, and ¾ NPK + ¼ until 11/4 dosages of Hortigro Rice fertilizer as a source of macronutrients N, P, K and micronutrients of Mn, Cu, Zn, B, and Mo. The treatments were arranged in a Randomized Block Design with 3 replications. Parameters observed during the research were plant height, tiller number, and yield of grain and straw of INPARI-32 lowland rice as crop indicator. The results showed that among other treatments, the highest plant height was resulted from the application of ¾ NPK-standard + ¼ Hortigro Rice, i.e. around 124 cm at 60 days after planting. The highest harvesting dry weight of grain and straw were observed in NPK-standard + 1/4 of Hortigro Rice fertilizer treatment, i.e. around 9.0 Mg ha-1 and 25.9 Mg ha-1, respectively. This yield showed a significant difference with ¾ NPK-standard combined with ¾ -11/4 dosages of Hortigro Rice. The highest dry weight of milled grains was resulted in the application of ¾ NPK-standard + 1/2 Hortigro Rice, i.e. around 7.3 Mg ha-1, which is significantly different from that in ¾ NPK-standard combined with 1.0 - 11/4 dosages of Hortigro Rice treatments, while the highest dry weight of straw was provided by NPK-standard, i.e. around 14.0 Mg ha-1. The highest dry weight of 1000 milled grains and ratio of dry weight of milled grain to straw were provided by ¾ NPK-standard + 1/2 Hortigro Rice around 32.0 gram and 0.63, respectively. The results indicated that the application of micronutrient fertilizer of Hortigro Rice in combination with NPK fertilizers can potentially increase lowland rice productivity due to the micronutrients content of Mn, Cu, Zn, B, and Mo in it.